Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Hoka Hoka Bento Cabang Kelapa Gading - Afanin, Sarah Muthia; Hermawan, Rudianto (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This research aims to determine the effect of the variables Service Quality (X1) and Price (X2) on Customer Satisfaction (Y) at Hoka Hoka Bento Kelapa Gading Branch. Data was collected through questionnaires distributed to 140 respondents and analyzed using IBM SPSS Statistics 27.The results of the analysis show that the average value of the Service Quality and Price variables is 4.32 and 4.28 respectively, which indicates the